Compartment Syndrome following Below-Knee Amputation. (21st February 2022) - Gerry, Adam S.; Christopher, Zachary K.; Patel, Karan; Kile, Todd A.; Bingham, Joshua S.
Abstract : In the setting of below-knee amputation, compartment syndrome is a rare complication. Early clinical symptoms of an acute compartment syndrome following below-knee amputation can mimic or be masked by postoperative pain management. We present the case of a 38-year-old male with a significant past medical history of Proteus syndrome who underwent an elective transtibial below-knee amputation. Following surgery, the patient had extensive postoperative pain and high pain medication requirements and returned to the operating room for irrigation and debridement due to suspicion of an infection. Upon return to the operating room to manage the infection, the necrotic tissue was discovered and removed which had developed due to a suspected missed acute compartment syndrome. The necrotic tissue secondary to the compartment syndrome subsequently resulted in infection. Multiple irrigation and debridement procedures were performed to further manage the infection, and ultimately, the patient was deemed stable for discharge. Acute compartment syndrome (ACS) following below-knee amputation (BKA) is a rarely documented but critical complication. This case describes the unique setting in which a compartment syndrome can be masked due to postoperative pain management and infection. Orthopedic surgeons should be aware of the varying risk factors and presentations of an acute compartment syndrome (ACS) as it can occur and is a devastating complication.